2003
DOI: 10.1038/sj.ijir.3900945
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen-mediated hormonal imbalance precipitates erectile dysfunction

Abstract: Declining testosterone (T) in an aging male offsets the equilibrium between androgen and oestrogen (oestradiol, E 2 ) with a resultant increase in E 2 -T ratio. Similar functional hormone imbalance is existent in clinical states of hypogonadism and is likely to arise from exposure of males to environmental oestrogens. The pathophysiological significance of this derangement on erectile function, hitherto unknown, was estimated in sexually mature male rats following acute and chronic treatment with oestrogen. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
(21 reference statements)
2
27
1
2
Order By: Relevance
“…Then, it was proposed that excess of estradiol could be responsible for sexual function and dysfunction in men (Cohen, 1998). And animal experiment with rats indicated that estrogen-mediated hormonal imbalance precipitates ED (Adaikan & Srilatha, 2003). Our data reported that no significant difference in testosterone levels had been found among ED patients and normal control groups, which is controversial to some previous studies (Srilatha & Adaikan, 2011).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Then, it was proposed that excess of estradiol could be responsible for sexual function and dysfunction in men (Cohen, 1998). And animal experiment with rats indicated that estrogen-mediated hormonal imbalance precipitates ED (Adaikan & Srilatha, 2003). Our data reported that no significant difference in testosterone levels had been found among ED patients and normal control groups, which is controversial to some previous studies (Srilatha & Adaikan, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, estrogens, in particular estradiol, regulate the initial part of the emission phase of ejaculation, a critical phase of ejaculation latency (Vignozzi et al, 2008). Rats with increased estradiol levels had significant prolongation of ejaculation latencies and impaired intracavernous pressure (Adaikan & Srilatha, 2003), and elevated estradiol and low testosterone levels are associated with the severity of ED (Srilatha & Adaikan, 2011). Here, we proposed that the homeostasis between estradiol and testosterone could be involved in orchestrating the regulation of male sexual function, and we aim to investigate the association between the hormonal profile and the incidence of PE, ED, or PE combined with ED.…”
Section: Introductionmentioning
confidence: 99%
“…In another study too, long-term therapeutic efficacy of tadalafil in improving International Index of Erectile Function scores and sexual function was correlated to increase in T/E 2 ratio (resulting more from E 2 decrease, rather than T increase). 52 There are also direct evidences from animal studies including dose-related inhibitory effect of intromission and postejaculatory mounting latencies by E 2 , 53 and reversal or normalisation of sexual function following E 2 withdrawal. 54 Taken together, it may be postulated that the opposing effects of androgen and oestrogen in sexual physiology may overlie a delicate 'yin yang' balance with the possibility of triggered cross-talk and functional derangement when the ratio is disturbed.…”
Section: Understanding Oestrogen Effects In the Malementioning
confidence: 99%
“…Several articles [1][2][3][4][5] concerning mechanistic studies in sex steroid hormones and sexual function/ dysfunction have been published recently in the IJIR: The Journal of Sexual Medicine, consistent with the contemporary nature of this physiological/ pathophysiological association. In 2001, Park et al 1 reported on three groups of female New Zealand White rabbits (control and bilateral oophorectomy with and without estrogen replacement).…”
mentioning
confidence: 94%